An Exploratory Study on Physical Fitness Policies Among Police Departments in North Carolina - Fortenbery, Jay (2016)
The purpose of this study was to examine the existing state of physical fitnessmaintenance policies among police departments in North Carolina, and how thosepolicies impact reported injuries among police officers. The research identified a sampleof police departments with and without mandated physical fitness maintenance policies(n = 145) for years 2013-2015 and through collaboration with the North Carolina Leagueof Municipalities, determined the number officer injuries per department for comparison.This information also included the cause of injury, costs, lost work days and claims bymale and female for comparison. A cross-sectional analysis and purposive samplingmethod were used to compare agencies who self-reported their level of physical fitnessmaintenance. Agencies were classified as mandated fitness standards, mandated wellnessstandards, and no standards. Police departments with mandatory physical fitnessstandards (FS) were found to have significantly lower medical costs (X² (1) = 126.4, p =.001, C = .541) and lost work days (X² (1) = 6.68, p = .009, C = .980) in several analysiswhen compared to agencies without FS and agencies with WS alone. Police departmentswith mixed standards (FS or WS or both) were compared to agencies without standardsand no statistical significance was found. Future studies are recommended to increase thegeneralizability of the study and to determine causes of the increases in medical costsobserved in agencies that mandate wellness standards